Future of e-Learning in Medical Education—Perception, Readiness, and Challenges in a Developing Country - Syed, Sabin; Rastogi, Aayushi; Bansal, Akanksha; Kumar, Ashish; Jindal, Ankur; Prakash, Arun; Agarwal, Gaurav; Varshney, Mohit (Frontiers in Education, 2021)
Background: Medical institutes in India and globally were widely affected by the COVID-19 pandemic, and there was an almost immediate need to adapt modules for delivery on e-learning platforms. This study was undertaken to gauge the future and usefulness of e-learning in medical education by analyzing the perception, attitude, and readiness of healthcare learners during the ongoing pandemic. Methodology: A quantitative survey was conducted among the healthcare community, during lockdown i.e., over a period of five weeks from 8th May to June 13, 2020. A survey questionnaire was developed to understand the demographic details, knowledge, infrastructure access, and attitude of the healthcare professionals. It was circulated through snow-balling technique with one hundred healthcare and allied professionals (linked with Project ILBS-ECHO) as the initial seeds. Each person was asked to then circulate the survey to 20 or more of their contacts and so on for the proposed duration of the study. Identifying information was anonymized before and ethical approval was obtained prior to initiating the survey. Results: A total of 3,004 healthcare professionals voluntarily participated in the survey. The respondents were mostly young adults, with 61% of participants being <30 years of age. About 65.41% used e-learning platforms for obtaining knowledge and skills during the pandemic, despite 71.1% of the respondent reporting cyber security concerns. Significant advantages of e-learning mentioned by participants was reduction in travel time and assistance in maintaining social distancing (68.21%) without compromising learning. Conclusion: With learners consistently jumping on to the bandwagon, the trend can be anticipated to continue post pandemic. For this reason, the study tried to highlight the awareness, perceptions, and potential challenges faced by Indian healthcare and allied professionals regarding e-learning as a method of education.